2012
DOI: 10.4067/s0718-95162012005000029
|View full text |Cite
|
Sign up to set email alerts
|

Effects of clay mineralogy and physico-chemical properties on potassium availability under soil aquic conditions

Abstract: Aquic conditions performed for paddy cultivation may cause many nutritional problems. Clay mineralogical composition plays an important role in this relation by affecting many physico-chemical and biological characteristics of soils. Three forms of K including unavailable, slowly available and readily available K, exist in equilibrium in the soil system. Relationships between soil potassium forms with the clay mineralogical suite and physico-chemical properties were determined in 33 soil samples collected from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 21 publications
0
16
0
Order By: Relevance
“…A combination of soil mineralogy, physicochemical properties and soil moisture regime gives a better insight into the effects of clay minerals on different forms of K in soil [64] [65] [66]. Raheb and Heidari [65] observed that non-exchangeable potassium in smectite-dominant soils was lower than those dominated by vermiculite, hydroxy-interlayered vermiculite and illite, and there were significant correlations between exchangeable potassium and clay content, organic carbon and cation exchange capacity. Similarly, Bajwa [64] observed that beidelitic clays can fix > 80% of K under aquic soil conditions.…”
Section: Nh +mentioning
confidence: 99%
“…A combination of soil mineralogy, physicochemical properties and soil moisture regime gives a better insight into the effects of clay minerals on different forms of K in soil [64] [65] [66]. Raheb and Heidari [65] observed that non-exchangeable potassium in smectite-dominant soils was lower than those dominated by vermiculite, hydroxy-interlayered vermiculite and illite, and there were significant correlations between exchangeable potassium and clay content, organic carbon and cation exchange capacity. Similarly, Bajwa [64] observed that beidelitic clays can fix > 80% of K under aquic soil conditions.…”
Section: Nh +mentioning
confidence: 99%
“…Similar to exchangeable K, the non-exchangeable K in the study area was also higher in surface soils than in subsurface soils and was significantly correlated with illite (Pearson correlation coefficient of 0.361), vermiculite (0.373), smectite (0.324), clay content (0.290), CEC (0.441), OC (0.277) and CCE (-0.447) (Table 4). Raheb and Heidari (2012) found that due to the thermal and moisture conditions for weathering of primary minerals, the exchangeable and non-exchangeable K contents in surface soils were higher than those in subsurface soils. In the study area, some representative pedons such as 51 (Alfisols), 33 (Alfisols), 36 (Molisols), 49 (Alfisols) and 39 (Vertisols) had the larger amount of non-exchangeable K in surface soils (956,699,690,680 and 541 mg/kg, respectively) and subsurface soils (892,421,389,463 and 541 mg/kg, respectively), while subsurface soils in the Entisols including pedons 53, 29, 34 and 47 had the lower amounts of non-exchangeable K. Alfisols in semi-arid regions are the most well-developed soils with moderate leaching.…”
Section: 32mentioning
confidence: 98%
“…It seems that organic matter plays a more important role than smectite mineral in retaining exchangeable K in the studied soils. Raheb and Heidari (2012) stated that the smectitic soils are rich in exchangeable K, whereas the predominant illite soils exhibit low amount of exchangeable K. In addition, there are significant correlations of exchangeable K with CEC and OC.…”
Section: Potassium (K) Formsmentioning
confidence: 99%
See 1 more Smart Citation
“…E-mail: mslalit@yahoo.co.in Author(s) agree that this article remain permanently open access under the terms of the Creative Commons Attribution License 4.0 International License in the soil (Havlin et al, 1999). Hence the K availability in the soil solution (intensity) and the inherent capacity of the soil to buffer this concentration against changes are among the important parameters that determine effective availability of K to plants (Grimme, 1976;Raheb and Heidari, 2012). In some cases even though the soil contain considerable amount of total K, the availability to plants are negligible.…”
Section: Introductionmentioning
confidence: 99%